PENTINGNYA PENDIDIKAN KARAKTER DI INDONESIA - Saefullah, Muhammad; Lailiyah, Siti; Mulyani, Tri (AL-QALAM: JURNAL KEPENDIDIKAN, 2022)
Character education is an effort that is designed and implemented systematically to help students understand the values ​​of human behavior related to God Almighty, oneself, fellow human beings, the environment, and nationality which are manifested in thoughts, attitudes, feelings, words. and actions based on religious norms, laws, etiquette, culture, and customs. The purpose of this study is to find out how important character education can be in education units in Indonesia as an effort to shape the personality of students who have a strong, religious and independent spirit. This research is a qualitative research with literature study method. The results of this study indicate that character education is very necessary in shaping the personality of students.